(untitled) (London Journal of Medical and Health Research, 2024)
Over time, neck lifting has undergone a notable evolution. Initially, techniques focused on treating the skin and subcutaneous cellular tissue (SCT), resulting in excessive tension on these structures, producing suboptimal results and unaesthetic scars. Over time, techniques involving plication of the platysma muscle (PM) in its lateral and medial regions were introduced, aiming to reposition deep structures through compression and tension. However, these approaches had limitations as the results tended to deteriorate quickly due to the stretching of the platysma fascicles. Today, a more advanced approach has been adopted in neck treatment, shifting from focusing on tension on the platysma to reducing deep structures. The deep neck lifting technique addresses the reduction of superficial and deep fat compartments, as well as the digastric muscles and the submandibular gland, avoiding excessive tension on the PM sutures. This methodology allows for more stable and long-lasting results over time.